2017
DOI: 10.1002/jcop.21918
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood and cultural stressors associated with delinquency in Latino adolescents

Abstract: We have no conflict of interest to declare. AbstractResearch has demonstrated a link between community violence exposure (CVE) and delinquency in adolescence, but little is known about the role of cultural stressors in this relation. This study examined the moderating role of acculturation dissonance and ethnic/racial discrimination in the link between CVE and delinquency engagement in a sample of Latino adolescents. Participants for this study included 134 Latino adolescents (46% males, mean age of 16.14, sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
(87 reference statements)
1
6
0
Order By: Relevance
“…Results from prospective studies indicated links between ECV and school drop‐out (Peguero, 2011), aggression (Williams et al., 2014), antisocial behavior (Schilling et al., 2007), weapon involvement (Kemal et al., 2018; Shetgiri et al., 2016), and high‐risk sexual behavior (Brady et al., 2008). Furthermore, there was also evidence of behavioral outcomes across both cross‐sectional and prospective studies that illustrated the links between ECV and behavior problems (Aisenberg, 2001; Foster & Brooks‐Gunn, 2013; Gudiño et al., 2011, 2012, 2018; Peinado et al., 2014; Ramos‐Olazagasti et al., 2013), delinquency or offending (Baskin‐Sommers et al., 2016; Gorman‐Smith et al., 2004; Isom Scott, 2018; Peacock et al., 2003; Rubens et al., 2018; Shukla & Weisner, 2016; Snyder & Merritt, 2014), and substance abuse (Bennett & Joe, 2015; Bermea et al., 2020; Brady et al., 2008, 2009; Cardoso et al., 2016; Goldbach et al., 2015; Poquiz & Fite, 2016; Ramos‐Olazagasti et al., 2017; Russell et al., 2016; Schilling et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from prospective studies indicated links between ECV and school drop‐out (Peguero, 2011), aggression (Williams et al., 2014), antisocial behavior (Schilling et al., 2007), weapon involvement (Kemal et al., 2018; Shetgiri et al., 2016), and high‐risk sexual behavior (Brady et al., 2008). Furthermore, there was also evidence of behavioral outcomes across both cross‐sectional and prospective studies that illustrated the links between ECV and behavior problems (Aisenberg, 2001; Foster & Brooks‐Gunn, 2013; Gudiño et al., 2011, 2012, 2018; Peinado et al., 2014; Ramos‐Olazagasti et al., 2013), delinquency or offending (Baskin‐Sommers et al., 2016; Gorman‐Smith et al., 2004; Isom Scott, 2018; Peacock et al., 2003; Rubens et al., 2018; Shukla & Weisner, 2016; Snyder & Merritt, 2014), and substance abuse (Bennett & Joe, 2015; Bermea et al., 2020; Brady et al., 2008, 2009; Cardoso et al., 2016; Goldbach et al., 2015; Poquiz & Fite, 2016; Ramos‐Olazagasti et al., 2017; Russell et al., 2016; Schilling et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…One study demonstrated prospective analyses indicating that ECV was linked to reduced political efficacy (Roy et al., 2019). Among the findings that illustrated links between ECV and physical health outcomes, one cross‐sectional study established an association with sleep problems (Rubens et al., 2018), whereas longitudinal studies revealed that ECV was related to survival expectations (Swisher & Warner, 2013; Warner & Swisher, 2015) and physical health or status (Russell et al., 2016; Swisher & Warner, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Limited research examines the role of safety concerns on Latinx adolescents’ well‐being, but other related neighborhood stressors are examined. For example, neighborhood disadvantage is associated with increased depression and anxiety symptoms (Rubens et al., 2018). With Mexican American youth, exposure to neighborhood violence was associated with more delinquency among those who experienced low levels of discrimination (Rubens et al., 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, neighborhood disadvantage is associated with increased depression and anxiety symptoms (Rubens et al., 2018). With Mexican American youth, exposure to neighborhood violence was associated with more delinquency among those who experienced low levels of discrimination (Rubens et al., 2018). Although a growing body of neighborhood effects literature with Latinx youth exists, there is a lack of representation of multiple Latinx ethnic groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Latinx adolescents, particularly those from low-income urban communities, experience higher rates of violence than non-Latinx youth (Shukla & Wiesner, 2016; Smokowski et al, 2009). Immigrant youth are at greater risk for violence exposure due to risk factors associated with the migration and postmigration process (Rubens et al, 2018) and when they settle into urban U.S. communities marked by crime and poverty (Brady et al, 2008; Jocson et al, 2018). In this sense, cultural considerations cannot be understood apart from larger societal constraints (Herrera & Agoff, 2018).…”
mentioning
confidence: 99%